Membangun Entrepreneur Mindset Masyarakat melalui Pelatihan Branding dan Digital Marketing - Prasetyo, Alfian Eko Widodo Adi; Khorini'mah, Shinta Melia; Eldi, Bastian; Fatoni, Nakhwa Kamilia; Qorbala, Moh. Zuhad; Oktavia, Riska; Sanuna, Muhammad Athar; Dewi, Gustianti (Al-Mu'awanah: Jurnal Pengabdian kepada Masyarakat, 2023)
The development of internet technology in the era of the industrial revolution 4.0 is getting faster. One of them is that the internet is used to develop a business. Entrepreneurship has an important role in economic growth. Entrepreneur mindset is very important to form because it is related to the mindset of an entrepreneur to adapt to the times. Improved branding and digital marketing skills are needed to realize a technologically advanced community economy. Therefore, KKN Tematik 108 group 15 UIN Sunan Kalijaga held branding and digital marketing training with the aim of building an entrepreneurial mindset to improve the economy, especially in Padukuhan Blekik. This service uses the PAR (Participatory Action Research) method with data collection techniques, namely observation, interviews, and documentation techniques. The targets in this service are the community, youth, and business actors totaling 45 people. The training was held at the Al-Huda Mosque in Blekik Village. This activity also presents competent speakers in the fields of academics and entrepreneurship. The results of this service are increasing knowledge and creating an entrepreneur mindset for the people of Padukuhan Blekik.